El consumo de drogas y su incidencia en el rendimiento académico de los estudiantes del primer año de bachillerato del colegio provincia del Carchi en el periodo lectivo 2015-2016 - Pazmiño Valdivieso, Irene Gertrudis (2015)
Drug use starts at a very early age, many factors that induce teenagers to try all kinds of toxic substances, in some cases, is the pleasure of experiencingthe effects hey have on the organism, in other by the influence of his friends/ as, the situation is that once you are immersed in this kind of addiction, it ishard to leave and rehabilitation. The consequences are harmful, affectingnegatively on their health, their family, social environment and education. Teens, who are in the world of drugs, change their behavior, emotions,aspirations, giving up studying and directly affecting their academic performance…..